2016
DOI: 10.1145/3004281
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent JavaScript Parsing for Faster Loading of Web Apps

Abstract: JavaScript is a dynamic language mainly used as a client-side web script. Nowadays, web is evolving into an application platform with its web apps, and JavaScript increasingly undertakes complex computations and interactive user interfaces, requiring a high-performance JavaScript engine. There have been many optimizations for efficient JavaScript engines, but one component that has not been optimized much is JavaScript parsing. A JavaScript function needs to be parsed before being executed, and the parsing ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…They showed that their prioritization scheme improved the PLT by 50% to 60% on 1GHz CPU phones. reducing payload with code splitting [118], concurrent parsing [119], and compiled code reusing [119] have been proposed to optimize the JavaScript loading, parsing and execution process. A study by Park et al [119] shows that concurrent parsing improves the web application loading performance by up to 32.7% and by 18.2% on average.…”
Section: Content Prioritizationmentioning
confidence: 99%
“…They showed that their prioritization scheme improved the PLT by 50% to 60% on 1GHz CPU phones. reducing payload with code splitting [118], concurrent parsing [119], and compiled code reusing [119] have been proposed to optimize the JavaScript loading, parsing and execution process. A study by Park et al [119] shows that concurrent parsing improves the web application loading performance by up to 32.7% and by 18.2% on average.…”
Section: Content Prioritizationmentioning
confidence: 99%
“…In this section we use a purposefully-simple web app as running example for describing each phase of Lacuna. The HTML code of the web app just includes the example.js script in Listing 6. it defines the a, b, and c functions (lines [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and calls a in line 15. When called, function a starts a 6-seconds timeout (lines 2-4), and function b prints a message in the browser console when the timeout is triggered (lines 3 and 7).…”
Section: The Approachmentioning
confidence: 99%
“…These nodes represent JavaScript functions that are not called by any other function (or from the global scope) according to all the different analysis techniques applied in the previous phase. We consider the global node as always alive since in JavaScript the global scope is always present and executed in a web app running in the browser 8 . By referring to Figure 3, in our running example the only node which is (i) different from the global one and (ii) unreachable from the global node is the one corresponding to the c function.…”
Section: Eliminationmentioning
confidence: 99%
See 2 more Smart Citations